Assessment of fungal toxins in the dairy value chain and potential risk to human health in Kenya - Kirino, Y.; Lindahl, Johanna F.; Makita, K.; Grace, Delia (2014)
Aflatoxins (AFs), carcinogenic byproducts of fungi contaminating maize and other crops, can be carried over into meat and milk when aflatoxin-contaminated crops are fed to livestock. People who consume such animal products are exposed to the toxins. To assess the aflatoxin contamination status in marketed raw milk and associated risk factors in a densely populated peri-urban area in Nairobi, a descriptive cross-sectional census in the Dagoretti Division was designed. Structured questionnaires were filled in by face-to-face interviews with raw milk retailers. Small portions of milk were purchased from each respondent and brought to laboratory for competitive ELISA tests for aflatoxin M1 (AFM1) detection. Geographic coordinates of each eligible retailer were recorded. A total of 350 milk retailers were visited and 344 were plotted on a map. Of them, 249 retailers answered the questionnaire and a milk sample from each of 200 retailers underwent ELISA test for AFM1. Overview of raw milk distribution system in Dagoretti revealed that there were 5 business types: kiosks (71%), dairy shops (21%), street or door-to-door vendors (3%) grocery stands (1%) and unidentified (4%), and their milk is mainly sourced directly from dairy farms (59%) or from intermediate distributors (35 %). The majority of retailers sell below 20 litres of un-boiled milk. The mean daily milk consumption was 940 ml in adults and 729 ml in children. Although 58 % of retailers have heard about aflatoxins and the majority of them agreed that AF can be present in milk, only 29 % claimed “milk safety cannot be judged by sight or taste” and only 6 % that “milk is not completely safe even after boiling”. The ELISA test found the mean concentration of AFM1 was 129 ± 16 (SE) ppt with maximum of 1,675 ppt. Of all, 55 % exceeded EU maximum level of 50 ppt and 6% exceeded Codex maximum level of 500 ppt. Compared to milk from street vendors, significantly higher AFM1 was detected in milk from kiosks and dairy shops, especially when the milk was sourced to from farms without intermediate distributor. Our findings indicate the importance of understanding natural or artificial processes which conditions AF concentration in milk along its distribution route.